Analisis Manajemen Pelaksanaan Standar Pelayanan Minimal (SPM) Orang Terduga TBC di Puskesmas Pringkuku Kabupaten Pacitan - Muradah Retyani, Amira; Paramita, Farah; Supriyadi; Herya Ulfah, Nurnaningsih (Jurnal Kesehatan, 2025)
Tuberculosis (TB) is one of the top 20 causes of death worldwide. In Indonesia, TB cases increased in 2022 and 2023 compared to 2021. Pacitan Regency, which ranks eighth lowest in TB case detection achievement in East Java, also experienced an increase in the number of cases in 2023. This increase can be addressed through the implementation of minimum health services for individuals suspected of having TB at all Community Health Centers, with a target achievement of 100%. However, not all Community Health Centers have provided optimal services. This includes Pringkuku Community Health Center in Pacitan Regency, which recorded a minimum service coverage of less than 50%. This study aims to analyze management implementation of the minimum service standards for suspected TB cases at Pringkuku Community Health Center, covering input and process aspects in 2023 and 2024, the output in 2024, along with the challenges encountered. The methods used included observation, in-depth interviews, and document review, utilizing interview guides and observation. The study was a qualitative research with a case study design, involving 8 key informants and 3 supporting informants. The data analysis produced ten main themes, indicating that health services in 2024 have not yet reached the 100% target. Major input-related barriers included the absence of a midwife in one village. In the process aspect, issues such as dual roles of program officers and negative community stigma were found. Therefore, support personnel and enhanced public education are needed to help achieve the 100% target. Keywords: community health center, management, minimum service standards, tuberculosis